CD73-Positive Small Extracellular Vesicles Derived From Umbilical Cord Mesenchymal Stem Cells Promote the Proliferation and Migration of Pediatric Urethral Smooth Muscle Cells Through Adenosine Pathway - Zhang, Shilin; Li, Jierong; Li, Chunjing; Xie, Xumin; He, Jun; Ling, Fengsheng; Li, Bowei; Wu, Huayan; Li, Zhilin; Zheng, Jianwei (Frontiers in Bioengineering and Biotechnology, 2022)
Smooth muscle cells (SMCs) are the main functional component of urethral tissue, but are difficult to proliferate in vitro. Mesenchymal stem cells (MSCs) and mesenchymal stem cell-derived small extracellular vesicles (MSC-sEV) have been shown to promote tissue repair by regulating the proliferation and migration of different types of cells. In this study, we investigated the effect of umbilical cord mesenchymal stem cell-derived sEV (UCMSC-sEV) on the proliferation and migration of pediatric urethral smooth muscle cells (PUSMCs) and the mechanism by which sEV regulates the function of PUSMCs. We observed that UCMSC-sEV can significantly promote the proliferation and migration of PUSMCs in vitro. UCMSC-sEV exerted proliferation and migration promotion effects by carrying the CD73 to PUSMCs and catalyzing the production of adenosine. Conversely, the effect of UCMSC-sEV on the proliferation and migration of PUSMCs were no longer observed with addition of the PSB12379 as a CD73 inhibitor. It was found that the phosphatidylinositol 3‑kinase (PI3K)/protein kinase B (AKT) signaling pathway in PUSMCs was activated by adenosine or UCMSC-sEV intervention. In summary, UCMSC-sEV promoted proliferation and migration of PUSMCs in vitro by activating CD73/ adenosine signaling axis and downstream PI3K/AKT pathway. Thus, we concluded that UCMSC-sEV may be suggested as a new solution strategy for the urethral tissue repair.